The Method for Quantitative Assessment of Sand-Drift Rate along the Southeastern Fringe of the Taklimakan Desert - Huang, Ning; Song, Yanhong; Xu, Lihang; Kuang, Qiong; Chen, Jian; Liu, Chao; Xie, Jianyong; xin, Guowei; Zhang, Jie (Journal of Environmental Accounting and Management, 2026)
Wind-blown sand disasters around the Taklimakan Desert have a great impact on the local residential environment and infrastructure. A quantifying sand-drift rate is essential for the local sand-control engineering. However, most studies investigate and evaluate the Drift Potential (DP) based on the wind information, which is convenient but may differ significantly from the actual sand-transport rate per unit width Q. Long-term wind-blown sand observation was carried out at the southeastern edge of the Taklimakan Desert, and six monitoring sites, with anemometers and sand containers, were set up within an 800 km area. The results show that a significant discrepancy exists between the DP and the measured Q. In order to assess the relationship between the DP and Q under the large differences in surface properties, three methods are proposed to assess the actual sand-transport rate per unit width Q. The first two methods (two Copula assessment models) are based on the Probabilistic Metric Space (PMS) theory. The models can evaluate the actual Q to at least 18.42%, when the DP is above 0.1 (DP is more than 7 VU_B (Vector Unit)). But the models are invalid for the evaluation of the real Q when the DP is below 0.1. The third method is to define the sand-drift factor C_i affected by the sand-particle characteristics and surface characteristics to be used to improve the existing framework of the DP to evaluate fully the real Q. It is an improved method for quantifying and predicting the blown-sand movement of the study area, which has been demonstrated to outperform the two Copula assessment models under lower DP.